The indigenisation of terrorism in India - Clarke, Ryan (2009)
Some of the most recent attacks in India, including the Mumbai outrage, involved at least logistical assistance from India citizens. However, considerable neglect of this reality, in the media and other wise, could undermine efforts to form an effective counter-terrorism strategy and develop functional partnerships with its neighbours.